2020
DOI: 10.4236/ym.2020.43018
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Influencing Factors of the Quality of Work Life of Nurses in Intensive Care Unit

Abstract: Objective: To investigate the current status and influencing factors of the quality of work life of nurses in Intensive Care Unit (ICU). Methods: A total of 243 ICU nurses from 6 general hospitals in Jingzhou were selected by convenient sampling method. Questionnaires were conducted with the general information questionnaire, Connor-Davidson Resilience Scale (CD-RISC) and Work-Related Quality of Life Scale-2 (WRQoL-2). Results: The total average score of the quality of work life of ICU nurses was (3.35 ± 0.44)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…It should be noted that international knowledge exchange and globalization standards might be contributing to a convergence in the nursing field, resulting in relatively similar QWL levels among nurses worldwide. Our results also indicated that the scores are slightly higher than those in China ( 41 , 42 ). This may be due to all participants were from Fuzhou, an area with advanced medical technology and a standardized management system for nurses.…”
Section: Discussionsupporting
confidence: 55%
“…It should be noted that international knowledge exchange and globalization standards might be contributing to a convergence in the nursing field, resulting in relatively similar QWL levels among nurses worldwide. Our results also indicated that the scores are slightly higher than those in China ( 41 , 42 ). This may be due to all participants were from Fuzhou, an area with advanced medical technology and a standardized management system for nurses.…”
Section: Discussionsupporting
confidence: 55%
“…The scores of the scale range from 33 to 165. The higher the score of the scale, the higher the quality of work life (Hu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Điều này cho thấy các NVYT ở Việt Nam hài lòng hơn với nơi làm việc và công việc của họ. Nhìn chung, JCS đóng một vai trò cực kỳ quan trọng đối với CLCSTCV [8], kết quả này cao hơn NVYT ở Trung Quốc (3,64 ± 0,50) [10]. Nghiên cứu của Nguyễn Hoàng Nam và cộng sự (2018), Vũ Quốc Thắng (2021) tại Việt Nam cũng chỉ ra JCS có điểm số cao nhất trong các khía cạnh khảo sát [5,6].…”
Section: Bàn Luậnunclassified